Configuring Check Point NGX VPN-1/FireWall-1 - Stephens, Robert (Information security consultant) (Syngress Pub., 2005)
Check Point NGX VPN-1/Firewall-1 is the major release of Check Point's flagship firewall software product. Many of the features focus on how to configure and manage Dynamic Routing rules, which are essential to keeping an enterprise network both available and secure. This book deals with the subject, Check Point.